Legal entity and legal capacity of a limited liability company - Shukrullaev Siyovush Ulugbek ugli (Genius Publishing Group, 2022)
This article discusses the problems and proposals in the practice of civil law regulation of the LLC, as well as the legal status and scope of responsibility of its founders, different approaches of scholars in this regard and the founding documents of the LLC and their registration, legal and legal capacity of the LLC. ziga specific properties are analyzed. The novelty of the study is the study of a wide range of problems, as well as scientifically based and important practical recommendations for improving the legislation in the field of improving the civil regulation of the LLC
Keywords: capital; Share; founder; possession